Endothelin receptor subtype A blockade does not affect the haemodynamic recovery from haemorrhage during xenon/remifentanil or isoflurane/remifentanil anaesthesia in dogs - Francis, Roland C. E.; Hoehne, Claudia; Klein, Adrian; Kaisers, Udo X.; Pickerodt, Philipp A.; Boemke, Willehad (Veterinary Anaesthesia and Analgesia, 2010)
Objective: To test the compensatory role of endothelin-1 when acute blood loss is superimposed on anaesthesia, by characterizing the effect of systemic endothelin receptor subtype A (ETA) blockade on the haemodynamic and hormonal responses to haemorrhage in dogs anaesthetized with xenon/remifentanil (X/R) or isoflurane/remifentanil (I/R). Study design: Prospective experimental randomized controlled study. Animals: Six female Beagle dogs, 13.4 ± 1.3 kg. Methods: Animals were anaesthetized with remifentanil 0.5 μg kg-1 minute-1 plus either 0.8% isoflurane (I/R) or 63% xenon (X/R), with and without (Control) the systemic intravenous endothelin receptor subtype A antagonist atrasentan (four groups, n = 6 each). After 60 minutes of baseline anaesthesia, the dogs were bled (20 mL kg-1) over 5 minutes and hypovolemia was maintained for 1 hour. Continuous haemodynamic monitoring was performed via femoral and pulmonary artery catheters; vasoactive hormones were measured before and after haemorrhage. Results: In Controls, systemic vascular resistance (SVR), vasopressin and catecholamine plasma concentrations were higher with X/R than with I/R anaesthesia at pre-haemorrhage baseline. The peak increase after haemorrhage was higher during X/R than during I/R anaesthesia (SVR 7420 ± 867 versus 5423 ± 547 dyne seconds cm-5; vasopressin 104 ± 23 versus 44 ± 6 pg mL-1; epinephrine 2956 ± 310 versus 177 ± 99 pg mL-1; norepinephrine 862 ± 117 versus 195 ± 33 pg mL-1, p < 0.05). Haemorrhage reduced central venous pressure from 3 ± 1 to 1 ± 1 cmH2O (I/R, ns) and from 8 ± 1 to 5 ± 1 cmH2O (X/R, p < 0.05), but did not reduce mean arterial pressure, nor cardiac output. Atrasentan did not alter the haemodynamic and hormonal response to haemorrhage during either anaesthetic protocol. Conclusions and clinical relevance: Selective ETA receptor blockade with atrasentan did not impair the haemodynamic and hormonal compensation of acute haemorrhage during X/R or I/R anaesthesia in dogs. © 2010 The Authors. Journal compilation © 2010 Association of Veterinary Anaesthetists.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Anaesthesia; Atrasentan; Catecholamines; Dog; Haemorrhage; Xenon